1998
DOI: 10.3141/1636-10
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Safety Effect of Raised Bicycle Crossings Using a New Research Methodology

Abstract: Before-and-after study methodology was developed and applied to evaluating the effect on bicyclists’ safety of raising urban bicycle crossings by 4 to 12 cm. In total, 44 junctions were reconstructed in this way in Gothenburg, Sweden. Four of these were studied in detail. Before the implementations, bicyclists were riding either in the roadway or on separate paths parallel to the roadway. The paths then ended with short ramps or curb cuts at each cross street, and bicyclists used nonelevated, marked bicycle cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 4 publications
2
42
0
Order By: Relevance
“…Scheepers et al, 2014;Wegman et al, 2012). In fact, good cycling infrastructure increases bicycle usage (Gårder et al, 1998). However, it is not always available.…”
Section: Introductionmentioning
confidence: 99%
“…Scheepers et al, 2014;Wegman et al, 2012). In fact, good cycling infrastructure increases bicycle usage (Gårder et al, 1998). However, it is not always available.…”
Section: Introductionmentioning
confidence: 99%
“…There have been junction based studies and these have found that reductions in risk for bicycle traffic may be obtained by specific features such as raised crossings (Gårder et al, 1998), careful design of the whole junction (Gårder et al, 1994) or by virtue of larger flows of bicycle traffic (Ekman, 1996;Wang and Nihan, 2004). Landis et al (2003) found that the perception of level of service for a straight on movement through a junction was related to running lane width, junction crossing width and volume of traffic.…”
Section: Introductionmentioning
confidence: 99%
“…The findings suggest that bike lane presence, crossing traffic volume, speed limit, speed parking, traffic signals, and crossing distance affect levels of service and comfort at intersections (Carter, Hunter, Zegeer , & Stewart, 2007) (Landis, Vattikuti, Ottenberg, Petritsh, Guttenplan, & Crider). In terms of the route, bicycle paths separated from traffic have been found to be preferred by users (Garder, Leden, & Pulkkinen, 1998) (Sener, Eluru, & Bhat, 2009) (Winters, Davidson, Kao, & Teschke, 2011). Models utilizing data from a smartphone app (ORcycle) that focuses on measuring comfort levels also show that traffic and commercial vehicles are the most important factors that decrease cyclists' comfort levels.…”
Section: Data Collection I: Multiple Subjectsmentioning
confidence: 99%
“…When the bicycle path is raised, the vehicles are likely to reduce their speed, thus reducing the risk of a crash. (Garder, Leden, & Pulkkinen, 1998). Dill et al (2007) identified that the perception about availability of comfortable bicycle facilities is a strong factor affecting bicycle ridership and bicycle mode share (Dill & Voros, 2007).…”
Section: Cyclists' Comfortmentioning
confidence: 99%
See 1 more Smart Citation